2018
DOI: 10.1103/physrevlett.121.163401
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Shielding of Ultracold Polar Molecules

Abstract: We use microwaves to engineer repulsive long-range interactions between ultracold polar molecules. The resulting shielding suppresses various loss mechanisms and provides large elastic cross sections. Hyperfine interactions limit the shielding under realistic conditions, but a magnetic field allows suppression of the losses to below 10 −14 cm 3 s −1 . The mechanism and optimum conditions for shielding differ substantially from those proposed by Gorshkov et al. [Phys. Rev. Lett. 101, 073201 (2008)], and do not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
146
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 47 publications
1
146
1
2
Order By: Relevance
“…Furthermore, Gorshkov et al suggested using combined static and microwave fields to achieve shielding by a repulsive second-order interaction, after precisely canceling the first-order interactions due to both fields [29]. While microwave shielding is feasible in static fields, the mechanism was later shown to be different and not reliant on precise cancellation of first-order interactions [27].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Gorshkov et al suggested using combined static and microwave fields to achieve shielding by a repulsive second-order interaction, after precisely canceling the first-order interactions due to both fields [29]. While microwave shielding is feasible in static fields, the mechanism was later shown to be different and not reliant on precise cancellation of first-order interactions [27].…”
mentioning
confidence: 99%
“…Next, we consider applying a static E-field along z , which lifts the degeneracy of m n = 0 and |m n | = 1 states, where m n is the z projection of the rotational angular momentum n. This Stark shift serves to shift the m n = 0 state, addressed by the spurious σ z polarization component, out of resonance while the microwaves are kept tuned to the m n = ±1 states. Under these conditions, this Hamiltonian effectively reduces to dressing with microwaves that are purely circularly polarized about a static external field, which has previously been demonstrated to realize effective shielding [27]. where the x and y axes are chosen as the semi-major and semi-minor axes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We are guided here by the results of [25], where the long-range shielding due to an electrostatic field was shown to suppress chemical reactivity as well as long-range inelastic scattering. Going ahead, it will of course be valuable to incorporate the influence of any potential chemical reactivity, for example by means of absorbing boundary conditions [26,27]. Scattering at long range is driven by the dipole-dipole interaction,…”
Section: The Scattering Hamiltonianmentioning
confidence: 99%